Application of STAD Approach in Differentiated Learning Assisted by Chromebooks to Improve Science Learning Outcomes in Class VI - Juli Putra Sinambela; Ryan Dwi Puspita (Jurnal Profesi Pendidikan, 2025)
This study is motivated by the need to improve the quality of teaching and student learning outcomes in elementary schools in the context of rapid technological development. The research aims to analyze the impact of implementing the Student Teams Achievement Divisions (STAD) approach in differentiated learning assisted by Chromebooks on the science learning outcomes of sixthgrade students at SD Negeri 2 Harian, Samosir. The STAD approach emphasizes cooperative learning and shared achievement, while differentiated learning accommodates students’ diverse needs in terms of content, process, and assessment. Chromebooks were utilized to support learning flexibility and access to digital resources. This study employed a descriptive qualitative method with a case study design. Data were collected through participatory observation, in-depth interviews, and analysis of students’ learning outcome documents. The research involved seven sixth-grade students with diverse learning characteristics. The results indicate that the integration of the STAD approach with Chromebookassisted differentiated learning increased student engagement, collaboration, and interaction during learning. Quantitative data showed that 85.7% of students achieved scores above the Minimum Completeness Criteria. In addition, qualitative findings revealed improvements in students’ critical thinking, problemsolving abilities, and digital literacy. In conclusion, integrating the STAD approach with Chromebooks creates a collaborative, adaptive, and effective learning environment that enhances science learning outcomes while fostering essential social and technological skills in elementary education.